2012
DOI: 10.1155/2012/829814
|View full text |Cite
|
Sign up to set email alerts
|

Noncytotoxic and Antitumour-Promoting Activities of Garcinia Acid Esters fromGarcinia atroviridisGriff. ex T. Anders (Guttiferae)

Abstract: The in vitro antitumour-promoting, cytotoxic, and antioxidant activities of two ester derivatives of garcinia acid, that is, 2-(butoxycarbonylmethyl)-3-butoxycarbonyl-2-hydroxy-3-propanolide (1) and 1′,1′′-dibutyl methyl hydroxycitrate (2), that had been previously isolated from the fruits of Garcinia atroviridis Griff. ex T. Anders (Guttiferae), were examined. Based on the inhibition of Epstein-Barr virus early antigen (EBV-EA) activation, compound 1 (IC50: 70 μM) showed much higher (8-fold) antitumour-promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The fruits, leaves, and stem bark extracts of G. atroviridis are found to be a rich source of bioactive secondary metabolites, including phenolic, flavonoid and tannin compounds such as xanthones (atroviridin), benzoquinones (atrovirinone), cambogin, garcinol, camboginal, triflavanone (garcineflavanone A) and biflavonols (garcineflavonol A) [ 20 , 21 , 22 ]. These phytochemicals have been reported to display diverse pharmacological activities including antioxidant [ 22 , 23 ], antimicrobial [ 23 , 24 ], anti-proliferative [ 17 , 23 , 25 ], anti-inflammatory [ 24 ], anti-cholinesterases [ 21 ] and anti-hyperlipidemic effects [ 20 ]. Interestingly, it has been reported that some of these phytometabolites such as phenolic compounds, were capable to transform inorganic silver ions into nanoparticles [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fruits, leaves, and stem bark extracts of G. atroviridis are found to be a rich source of bioactive secondary metabolites, including phenolic, flavonoid and tannin compounds such as xanthones (atroviridin), benzoquinones (atrovirinone), cambogin, garcinol, camboginal, triflavanone (garcineflavanone A) and biflavonols (garcineflavonol A) [ 20 , 21 , 22 ]. These phytochemicals have been reported to display diverse pharmacological activities including antioxidant [ 22 , 23 ], antimicrobial [ 23 , 24 ], anti-proliferative [ 17 , 23 , 25 ], anti-inflammatory [ 24 ], anti-cholinesterases [ 21 ] and anti-hyperlipidemic effects [ 20 ]. Interestingly, it has been reported that some of these phytometabolites such as phenolic compounds, were capable to transform inorganic silver ions into nanoparticles [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several interesting natural product compounds were isolated from local medicinal plants such as damnacanthal from Morinda elliptica that was reported to have anti-HIV and immunomodulating activities [12–15], goniothalamin from Goniothalamus spp. that was cytotoxic towards leukemic cells and also induced apoptotic cell death [16, 17], as well as phytosterols from Coleus tuberosus , garcinia acid esters from Garcinia atroviridis, and girinimbine from Murraya koenigii that were reported to have antitumour promoting activities [1820]. In this paper, we reported that the crude methanolic extract of C. cauliflora whole fruit has a very significant cytotoxicity towards promyelocytic leukemia HL-60 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Findings reported from elsewhere have indicated that G. atroviridis acid ester derivatives containing HCA were non-cytotoxic in CEMSS (human T-lymphoblastic leukemia) cells and Raji (human B-lymphoblastoid) cells. 29 On the other hand, exposure of 3T3 fibroblast …”
Section: Discussionmentioning
confidence: 99%